Methodology for a sustainable rehabilitation - Almeida, Manuela Guedes de (2004)
This work intends to show a methodology developed for the identification and resolution of buildings rehabilitation problems. The main goal of the present methodology is to support and help the decision-makers in order to achieve a capable and sustainable resolution of present problems, without compromising the needs for future interventions. This kind of tools is fundamental to avoid current mistakes and errors. In Portugal this type of tools is scarce. This methodology consists of a database system containing the available information concerning all the parameters involved in the rehabilitation process. The developed methodology was implemented with the assistance of a computational system developed from the start which, by means of pre-established relationships, allows the identification of the best intervention solutions and rehabilitation works to be carried out.